Will liquid biopsies improve outcomes for patients with small-cell lung cancer?. Issue 9 (September 2018) - Blackhall, Fiona; Frese, Kristopher K; Simpson, Kathryn; Kilgour, Elaine; Brady, Ged; Dive, Caroline
Summary: Small-cell lung cancer (SCLC) is an aggressive tumour that seeds metastases early with dismal outcomes. As expected from a disease that is closely associated with smoking, mutation burden in SCLC is high. Intratumoral and intertumoral heterogeneity is a substantial obstacle to successful treatment and the SCLC genomic landscape reveals few targets that are readily druggable. Chemotherapy elicits responses in most patients with SCLC, but their effects are short lived. Multiple clinical trials have been unsuccessful in showing positive survival outcomes and biomarkers to select patients and monitor responses to novel targeted treatments have been lacking, not least because acquisition of tumour biopsies, especially during relapse after chemotherapy, is a substantial challenge. Liquid biopsies via blood sampling in SCLC, notably circulating tumour cells and circulating free tumour DNA can be readily and repeatedly accessed, and are beginning to yield promising data to inform SCLC biology and patient treatment. Primary cell cultures and preclinical mouse models can also be derived from the relatively plentiful SCLC circulating tumour cells providing a tractable platform for SCLC translational research and drug development.